"BRIGHT GLANCES" OR "CLEVER HANDS"? THE DOMESTIC IMAGE OF WORKING-CLASS WOMEN IN ELIZA COOK'S JOURNAL. Issue 4 (4th November 2016) - Yan, Shu-chuan
Abstract : These lines, taken from the poem "Sweet Home, " were published by Eliza Cook (1818–89) in Once a Week in 1867. Accompanied by Joseph Swain's engraving (Figure 4 ), the poem presents an idealized portrait of a middle-class family in the nineteenth century. The home is a "blissful, holy place" where "Manhood, Infancy, and Age" can find their "love and peace" as well as "joy and grace." Of particular interest is that Swain places the female figures – grandmother, mother with a child on her lap, and daughter – at the center of the engraving: their bodies and faces are clearly sketched, whereas father and son, the only two male figures in the engraving, merely show half their faces with their backs turned to the reader. Overall, the poem itself contains some of the striking echoes of the dominant ideology of home at the time. The scene of the family gathered around the hearth illuminates the all-embracing concept of domesticity – coziness, comfort, and intimacy.